2002
DOI: 10.1073/pnas.132605599
|View full text |Cite
|
Sign up to set email alerts
|

DNA containing CpG motifs induces angiogenesis

Abstract: New blood vessel formation in the cornea is an essential step in the pathogenesis of a blinding immunoinflammatory reaction caused by ocular infection with herpes simplex virus (HSV). By using a murine corneal micropocket assay, we found that HSV DNA (which contains a significant excess of potentially bioactive ''CpG'' motifs when compared with mammalian DNA) induces angiogenesis. Moreover, synthetic oligodeoxynucleotides containing CpG motifs attract inflammatory cells and stimulate the release of vascular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 31 publications
5
60
0
Order By: Relevance
“…The heat-stable TLR9-dependent stimulus is most likely viral DNA. Indeed, high concentrations of isolated HSV DNA have been shown to be stimulatory (17,30). The TLR9-independent mechanism of HSV-1 recognition is not fully elucidated, but two different mechanisms could be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…The heat-stable TLR9-dependent stimulus is most likely viral DNA. Indeed, high concentrations of isolated HSV DNA have been shown to be stimulatory (17,30). The TLR9-independent mechanism of HSV-1 recognition is not fully elucidated, but two different mechanisms could be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with XLA are known to be susceptible to herpes viruses such as HHV-6, varicella-zoster, herpes simplex, and cytomegalovirus (29). Herpes viruses have been shown to contain unmethylated CpG motifs (30), and according to one study carried out on 96 XLA patients, herpes simplex virus infections represented 37% of all viral infections (31,32). An impairment in TLR9 signaling due to the defect in Btk may help explain this susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…30 The mechanisms underlying the enhanced inflammation are not precisely known, but preclinical data regarding herpetic stromal keratitis in wild-type HSV 1 infection revealed that angiogenesis may be induced by paracrine effects resulting from release of VP22 or the CpG motifs in the DNA of HSV 1, which are required for viral replication. [57][58][59][60] Most of these stimuli, especially the CpG motif, potently stimulate secretion of vascular endothelial growth factor (VEGF) A. [58][59][60][61] In addition, antiangiogenic molecules such as thrombospondin 1 and 2 are reduced in wild-type HSV 1 infection.…”
Section: X400 X400mentioning
confidence: 99%
“…[57][58][59][60] Most of these stimuli, especially the CpG motif, potently stimulate secretion of vascular endothelial growth factor (VEGF) A. [58][59][60][61] In addition, antiangiogenic molecules such as thrombospondin 1 and 2 are reduced in wild-type HSV 1 infection. 59 Many studies have shown that VEGF A is upregulated in HSV 1 infections; [62][63][64] thus, VEGF A may be the factor underlying the angiogenesis seen in our study.…”
Section: X400 X400mentioning
confidence: 99%